Pelatihan Pembelajaran Berbasis Projek dengan Kegiatan Eco-enzyme untuk Mendukung Implementasi Kurikulum Merdeka - Annisa Putri Noerviana; Rika Novia Mariska; Nur Vita Sari Eka Ramadhani; Nadia Putri Septiana; Citra Citra; Rosyida Nurul Anwar (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2023)
The negative impact of burning waste on the environment can disrupt the environmental balance. Waste management can be part of project-based learning, part of the independent curriculum. The waste generated can be useful and provide real learning experiences for students caring for the environment. Utilizing waste or organic waste such as peels of fruits and vegetables can be processed into Eco-enzymes. The activity aims to provide project-based learning training with eco-enzyme activities to support the implementation of the independent curriculum. This community service activity uses the training method in which participants practice after delivering material by the executor. Participants in the activity were school principals, teachers, and guardians at PAUD institutions in Cluster 1 Sawahan District, with 20 participants. The results of the implementation of the activity provide an overview to the teacher on how to carry out project-based learning with eco-enzyme activities as part of the utilization of waste to provide real learning experiences to students